Exploring communication management strategies in managing communication crisis: A qualitative study in Malaysia’s service sector - Ahmad, Nurbarirah; Tengku Mahamad, Tengku Elena; Tew Abdullah, Muhammad Hakimi; Sakarji, Siti Rosnita (Journal of Islamic, Social, Economics and Development, 2026)
Communication crisis inside organizations can profoundly impact employee performance, satisfaction, and organizational stability. This study investigates the function of communication management methods in mitigating communication crisis among customer care officer in Malaysia's service industry. Efficient communication management guarantees the precise and timely delivery of pertinent information, so enhancing job satisfaction, bolstering employee commitment, and diminishing turnover intentions. A qualitative study methodology was employed to investigate employees' experiences during communication crises. Data were gathered via comprehensive interviews with eighg individuals from various service sectors in Malaysia. The interview data were transcribed and analyzed with ATLAS.ti to discern important themes pertaining to communication management methods in emergencies. The findings underscore the significance of organized communication tactics in alleviating adverse effects, including employee stress, anxiety, and diminishing morale. This study presents a Communication Management Strategies Model to assist organizations in more successfully handling internal communication crises based on these findings. The proposed paradigm offers pragmatic insights for public and private sector organizations aiming to enhance crisis communication and elevate employee happiness.